Fiscal Federalism and Diversity Accommodation in Multilevel States (Springer Nature, 2024)
This open access edited book connects two strands of federal studies, fiscal federalism, and diversity accommodation, to answer two closely interrelated questions. The first of these is to what extent has the need to accommodate diversities determined financial relations and their evolution? The authors answer this question by conducting a thorough investigation of the types of diversity that drive such evolution. The second question is does fiscal federalism have a broadly positive or negative impact on the accommodation of diversities, by producing institutional solutions that either integrate a federal system or pull it apart? Through contributions from experts in law, economics, and political science, the book uses a series of case studies to establish a theoretical framework for exploring the relationship between fiscal federalism and diversity accommodation. The authors lay the groundwork for a comparative study of this relationship in multilevel states.